Proton irradiation tests of single crystal diamond detector at CIAE. (January 2020) - Liu, You-hang; Loh, Chang-wei; Zhang, Jia-liang; Wu, Fang-liang; Qi, Ming; Hei, Li-fu; Lv, Fan-xiu; Lv, Yin-long; Ge, Tao; Li, Yao-qian; Fu, Zhen-hui
Highlights: We have studied the radiation hardness of single crystal diamond detector under the irradiation of 100 MeV protons up to the fluence of 1.6 × 1017 protons/cm2. The maximum response current exceeded one milliampere in our experiment. We also present a statistical theory for trying to obtain the best fitting curve. Abstract: Single crystal diamond (SCD) detector is considered a candidate for the upgrade of Forward Calorimeter (FCal) in the foreseen HL-LHC. In order to investigate their radiation hardness, two SCD detectors were irradiated with 100 MeV protons up to the fluence of 1.6 × 10 17 protons/cm 2 and their response current was measured continuously. At the end of the irradiation period, the diamond detector could still maintain function and its residual signal reduced to 5% of the initial value approximately. The maximum response current of diamond detectors exceeded one milliampere under the irradiation of one-microampere proton current. In addition, a statistical theory is presented in an attempt to obtain the best fitting curve of the response of diamond detectors.